Exploring the Concept of Hope and Aspirations of Children in Conflict with the Law (CICL) - Bulatao, Aimee Ruth Y. (Philippine Social Science Journal, 2023)
Having hope and aspirations can serve as a driving force for children to have a flourishing life. This study aimed to explore the concept of hope and aspirations of Children in Conflict with the Law (CICL). There were 10 CICLs of the Regional Rehabilitation Center for Youth (RRCY) in Urayong, Bauang, La Union, who participated in the study. A semi-structured interview was used to gather data. Thematic analysis was also employed to analyze the data gathered. Based on the findings of the study, the CICL’s concept of hope includes positivity despite adversity, drawing strength from God, and having a positive social support system. Likewise, for CICLs aspirations, two themes were generated: future career and occupational fulfillment; and reform and acceptance. With this, the findings emphasized that despite being stigmatized by society, CICLs are still hopeful about life and aspire to become better individuals.